Pengaruh Metode Pembelajaran Tanya Jawab Terhadap Hasil Belajar Bahasa Indonesia Siswa Kelas III SD Negeri 097325 Bandar Siantar - Debora Yosevine Manurung; Jumaria Sirait (Departement of Mathematics Education, 2023)
This study aims to find out whether the Question and Answer Learning Method Has an Effect on the Indonesian Language Learning Outcomes of Grade III Students at SD Negeri 097325 Bandar Siantar or not. There are 2 hypotheses in this study, namely, (1) there is an effect of the application of the question and answer method on the learning outcomes of class III students of SD Negeri 097325 Bandar Siantar (H1) and there is no effect of applying the question and answer method on learning outcomes of Indonesian language students of class III SD Negeri 097325 Bandar Siantar (Ho). This research method is an experimental method with the type of Pre-Experimental Design research that uses the One Group Pretest-Posttest Design. The population of this study were all 25 students of grade III SD Negeri 097325 Bandar Siantar. Because the total population is less than 50, the population is used as the sample in this study. Data collection was carried out by giving tests and observation techniques. The research data were analyzed using descriptive analysis and inferential analysis. Based on the results of data analysis it is known that the tcount is 6.91 with a significant level of 0.05. So it can be concluded that there is an influence of the question and answer method on the results of learning Indonesian in class III SD Negeri 097325 Bandar Siantar. This means that H1 is accepted and Ho is rejected..